Sol gel derived MnTi doped Co2 W-type hexagonal ferrites: Structural, physical, spectral and magnetic evaluations. Issue 6 (15th April 2020) - Akhtar, Majid Niaz; Javed, Sumbal; Ahmad, Mukhtar; Sulong, A.B.; Khan, Muhammad Azhar
Abstract: W-type BaSr Co2 hexaferrites doped with Mn and Ti of the following composition Ba0.5 Sr0.5 Co2 Mnx Tix Fe16-2x O27 (x = 0.00, 0.50, 1.00, 1.50, 2.00, 2.50) were synthesized by sol-gel auto ignition method. The structure, phase, spectral bands, microstructure, and magnetic behaviors of the MnTi doped BaSr Co2 W-type ferrites were determined using XRD, FTIR, FESEM, and VSM respectively. Structural and physical parameters such as lattice parameters 'a' and 'c', crystallite size, cell volume, micro strain, porosity, bulk and X-ray density of the MnTi doped BaSr Co2 W-type hexaferrites were evaluated. The detailed and refined structural properties were determined using the Rietveld refinement of the MnTi doped BaSr Co2 W-type hexagonal ferrites. MAUD software was used for the refinement of the MnTi doped BaSr Co2 W-type hexagonal ferrites patterns. Rb, Rwp and Rexp values were found in the range of 10–19 for MnTi doped BaSr Co2 W-type hexagonal ferrites. The force constants at respective sites were also investigated through FTIR studies. FESEM images showed the hexagonal shape of the MnTi doped hexaferrites. Magnetic properties were estimated from the hysteresis loops recorded by VSM. The magnetic properties were decreased with the MnTi doping. However, anisotropic field was also found to be decreased with MnTi doping. This might be due to the ionic radii and nonmagnetic substitution of Ti in BaSr Co2 W-type hexagonal ferrites. The low coercivity values of these ferrites suggest the use of MnTi doped BaSr Co2 W-type ferrites for microwave absorption, memory devices and magnetic radar absorbing materials (MRAMs) in high frequency regime.